An Active and Heterogeneous Catalyst for Synthesis of Diphenyl Carbonate - Wang, Liping; Wang, Gongying; Wang, Fan (Asian Journal of Chemistry, 2015)
Zn4O[(O2C)-C6H4-(CO2)]3 was prepared by solvothermal method and characterized with XRD and FT-IR. Zn4O[(O2C)-C6H4-(CO2)]3 was used as the catalyst for the synthesis of diphenyl carbonate via the transesterification dimethyl carbonate and phenol and its catalytic activity was compared with Ti(OBu)4, Mg-Al Mg-Al LDH and Zn-Al Mg-Al LDH. The results show that Zn4O[(O2C)-C6H4-(CO2)]3 is an active and heterogeneous catalyst for the synthesis of diphenyl carbonate via the transesterification.